Respuesta :

Lets get started :)

f(x) = [tex] \frac{1}{9}x [/tex] - 2
 y   = [tex] \frac{1}{9}x[/tex] - 2
This is the original equation, and now we have to find the inverse.

When finding the inverse, just flip the variables, x as y and y as x

f ⁻¹(x) 
  ↓
x = [tex] \frac{1}{9}y [/tex] - 2
We have to isolate y as it is our f ⁻¹(x)

Take 2 to the other side { When you see subtraction, you do addition }
x + 2 = [tex] \frac{1}{9} y[/tex]

Take 9 to the other side { When you see division, you do multiplication }
9 ( x + 2 ) = y
9x + 18 = y

f ⁻¹ (x) = 9x + 18


ACCESS MORE